Two Mechanisms of Sensorimotor Set Adaptation to Inclined Stance - Lee, Kyoung-Hyun; Baksh, Asheeba; Bryant, Alyssa; McGowan, Mollie; McMillan, Ryan; Chong, Raymond K. (Frontiers in Human Neuroscience, 2017)
Orientation of posture relative to the environment depends on the contributions from the somatosensory, vestibular and visual systems mixed in varying proportions to produce a sensorimotor set. Here we probed the sensorimotor set composition using a postural adaptation task in which healthy adults stood on an inclined surface for three minutes. Upon returning to horizontal surface, participants displayed a range of postural orientations – from an aftereffect that consisted of a large forward postural lean to an upright stance with little or no aftereffect. It has been hypothesized that the post-incline postural change depends on each individual's sensorimotor set: whether the set was dominated by the somatosensory or vestibular system: Somatosensory dominance would cause the lean aftereffect whereas vestibular dominance should steer stance posture towards upright orientation. We investigated the individuals who displayed somatosensory dominance by manipulating their attention to spatial orientation. We introduced a distraction condition in which subjects concurrently performed a difficult arithmetic subtraction task. This manipulation altered the time course of their post-incline aftereffect. When not distracted, participants returned to upright stance within the three-minute period. However, they continued leaning forward when distracted. These results suggest that the mechanism of sensorimotor set adaptation to inclined stance comprises at least two components. The first component reflects the dominant contribution from the somatosensory system. Since the postural lean was observed among these subjects even when they were not distracted, it suggests that the aftereffect is difficult to overcome. The second component includes a covert attentional component which manifests as the dissipation of the aftereffect and the return of posture to upright orientation.